2011
DOI: 10.1007/s00432-011-1064-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety study of axillary reverse mapping in the surgical treatment for breast cancer patients

Abstract: Crossover between breast and ipsilateral arm lymphatic drainage system contributes for ipsilateral arm lymph node metastasis. When ARM and SLNB are simultaneously performed in a patient, selectively preservation of the ARM nodes that do not coincided with SLNs would be safe, even if the SLNs are positive. Pathological lymph node status does not account for the occurrence of metastasis in ARM nodes. ARM nodes could be preserved safely, independent of the pathological lymph node status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…Boneti et al 34 reported that crossover (ARM node ¼ SLN) occurred in only 6 (2.8%) of 218 patients, although ARM lymphatics were near or within the SLN biopsy field in 40.6% of patients. Nevertheless, other investigators reported concordance rates of 7.2%~28% between ARM nodes and SLN 14,16,19,20,26,27,30 (Table 2). In our recent study using fluorescence imaging, the ARM nodes were SLN-ARM nodes in 64 (27%) of 238 patients (unpublished data).…”
Section: Locations Of Sln and Arm Nodesmentioning
confidence: 90%
See 2 more Smart Citations
“…Boneti et al 34 reported that crossover (ARM node ¼ SLN) occurred in only 6 (2.8%) of 218 patients, although ARM lymphatics were near or within the SLN biopsy field in 40.6% of patients. Nevertheless, other investigators reported concordance rates of 7.2%~28% between ARM nodes and SLN 14,16,19,20,26,27,30 (Table 2). In our recent study using fluorescence imaging, the ARM nodes were SLN-ARM nodes in 64 (27%) of 238 patients (unpublished data).…”
Section: Locations Of Sln and Arm Nodesmentioning
confidence: 90%
“…However, the involved ARM node was the SLN in 7 of these 9 patients (Table 1). Deng et al 16 also reported that all ARM nodes were not involved, even in 12 patients with positive SLNs, among 50 of 69 patients whose ARM nodes did not coincide with SLNs. In the remaining six patients, all metastatic ARM nodes coincided with SLN-ARM nodes.…”
Section: Locations Of Sln and Arm Nodesmentioning
confidence: 92%
See 1 more Smart Citation
“…Due to oncological concern, therefore, ARM lymphatics/nodes within the boundaries of a standard ALND should be resected in these patients. On the other hand, In cN0 patients, the metastatic ARM nodes may be actually SLN-ARM nodes [3]. Deng et al [3] reported that ARM nodes metastasis occurred in 6 of 69 patients.…”
mentioning
confidence: 99%
“…On the other hand, In cN0 patients, the metastatic ARM nodes may be actually SLN-ARM nodes [3]. Deng et al [3] reported that ARM nodes metastasis occurred in 6 of 69 patients. In these 6 patients, all metastatic ARM nodes coincided with SLN-ARM nodes.…”
mentioning
confidence: 99%